2019
DOI: 10.1002/cne.24604
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular microglial cells interact with dividing precursor cells in the nonhuman primate and rodent prenatal cerebral cortex

Abstract: Cortical proliferative zones have been studied for over 100 years, yet recent data have revealed that microglial cells constitute a sizeable proportion of ventricular zone cells during late stages of cortical neurogenesis. Microglia begin colonizing the forebrain after neural tube closure and during later stages of neurogenesis populate regions of the developing cortex that include the proliferative zones. We previously showed that microglia regulate the production of cortical cells by phagocytosing neural pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
(84 reference statements)
2
26
0
Order By: Relevance
“…In both humans and nonhuman primates, the proliferative zones of the prenatal cortex are populated by neurogenic precursor cells including Pax6 + radial glial cells, Tbr2 + intermediate progenitor cells, Pax6 + translocating radial glial cells, Pax6 + astroglial precursor cells, and oligodendroglial precursor cells (Martínez-Cerdeño et al 2012;Cunningham et al 2013a,b). Our prior studies have also shown that there is more extensive microglial colonization and phagocytosis of neural precursors in fetal human and rhesus monkey brains when compared with other species such as rats (Barger et al 2019;Noctor et al 2019).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In both humans and nonhuman primates, the proliferative zones of the prenatal cortex are populated by neurogenic precursor cells including Pax6 + radial glial cells, Tbr2 + intermediate progenitor cells, Pax6 + translocating radial glial cells, Pax6 + astroglial precursor cells, and oligodendroglial precursor cells (Martínez-Cerdeño et al 2012;Cunningham et al 2013a,b). Our prior studies have also shown that there is more extensive microglial colonization and phagocytosis of neural precursors in fetal human and rhesus monkey brains when compared with other species such as rats (Barger et al 2019;Noctor et al 2019).…”
Section: Introductionmentioning
confidence: 71%
“…In the normally developing fetal rhesus monkey, proliferative cortical neural precursor cells reside in the ventricular zone (VZ) adjacent to the lateral ventricle, and in the subventricular zone (SVZ) that is superficial to the VZ (Smart et al 2002;Martínez-Cerdeño et al 2012;Cunningham et al 2013a). In the second trimester mitotic neural precursor cells produce cortical neurons destined for cortical layers 4 and 5 (Rakic 1974), microglial cells begin to colonize cortical proliferative zones (Cunningham et al 2013b), fetal microglia interact closely with mitotic neural precursor cells, and they regulate the size of the precursor cell pool through cellular phagocytosis (Cunningham et al 2013b; Barger et al 2019;Noctor et al 2019). Microglia-a specialized population of macrophage-like cells in the central nervous system (CNS) (Kettenmann et al 2011;Bachiller 2018)-display the morphological phenotype of "activated" cells in the normally developing fetal rhesus cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, microglia also modulate postnatal neurogenesis in the cortical subventricular zone (SVZ) [15] and hippocampus [16], influence cortical neuronal survival [17], and induce apoptosis and phagocytosis of cleaved caspase 3 (CC3) positive Purkinje cells in the postnatal mouse cerebellum [18]. In contrast, in the fetal brain, microglia align themselves adjacent to NPCs (neural progenitor cells) and promote their differentiation into intermediate precursor cells [19,20]. Microglia are shown to be involved in maintaining healthy NPC populations in the embryonic cortex and actively engulf NPCs within cortical proliferative zones as a mechanism to eliminate NPCs at the termination of neurogenesis [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, microglial regulation of neurogenesis, proliferation, differentiation and survival of neural precursors or migration are active processes even at embryonal stages (Aarum et al, 2003b; Bilimoria and Stevens, 2015; Cunningham et al, 2013; Erblich et al, 2011; Ueno et al, 2013), often affecting more immature progenitors. Nevertheless, somatic interactions have already been observed between microglial processes and the cell bodies of dividing neuronal progenitors (Cunningham et al, 2013; Noctor et al, 2019; Penna et al, 2020), thus, it needs to be addressed whether these are also functioning as somatic junctions. Secondly, at this stage we concentrated on the molecular and structural assessment of somatic microglia-neuron junctions, since to extend our experiments towards functional directions we would either need to manipulate immature neurons at different maturational stages, or to apply microglia-specific interventions at multiple developmental stages, clearly surpassing the scope of this study.…”
Section: Discussionmentioning
confidence: 99%